Perancangan Quality Plan untuk Penurunan Tingkat Kecacatan Produk di PT. Sentosa Alloy Industri - Susanto, Gunedi; Rahardjo, Jani (Jurnal Titra, 2013)
PT. Sentosa Alloy Industri is a company which engaged in spare part manufacture field of motorcycle. This company produces velg, hub, flange, brake handle. The purpose of this study is to devise improvements proposed and quality plan in die casting process which aims to reduce the level of defects and improve the product quality.The result of this study are: the level of porous defects 4,38%,Â  the level of imperfect product defects 2,08%, the level of sticky product defects 1,43%, and the smallest level of defects is cracked with 0,04%. Potential problem can be identified and analyzed using fishbone and Failure Mode and Effect Analysis method. The improvements proposed to get are got from the highest Risk Priority Number value (RPN), which occurs in Machine (RPN = 128), Method (RPN = 112), Man (RPN = 112), and Material (RPN = 72)